Bottlenecks of LNG supply chain in energy transition: A case study of China using system dynamics simulation. (1st July 2022) - Yin, Yuwei; Lam, Jasmine Siu Lee
Abstract: Natural gas plays a strategic role in energy transition. For instance, the Chinese government regards coal-to-gas transition as a medium-term emission mitigation option, resulting in growths in Liquefied Natural Gas (LNG) shipping import volumes. However, LNG terminal receiving capacity and domestic tanker fleet capacity insufficiencies become bottlenecks impacting LNG supply efficiency and security. This study analyses to which extent LNG shipping import growth accelerates under natural gas consumption growth, domestic production reduction and pipeline import reduction scenarios, then evaluates LNG terminal capacities and tanker fleet capacities needed to accommodate the respective LNG import volumes. An innovative System Dynamics model is developed based on historical data, policies and market information using China as a case. It found that consumption growths or alternative supply reductions by over 5% beyond the baseline simulation will cause LNG terminal overloads. Even in the baseline scenario without any unexpected supply or demand change, China's domestically owned LNG tankers only meet 49% of its LNG shipping import demand. Hence, the government is recommended to coordinate national energy strategies and sector-level planning. Terminal operators need to accelerate capacity expansions. Domestic shipping companies can invest in large-sized tankers to reduce LNG tankers deployed and relieve the dependency on foreign fleets. Highlights: Limited LNG terminal and fleet capacities hinder coal-to-gas transition of China. China's terminal capacities are insufficient to cope with unexpected demand surges. China's domestic tanker fleet can accommodate below 50% of LNG import volumes. Government needs to coordinate national energy policies and sector-level planning. Encouraging more players to invest in terminals and large ships are key solutions.